2015
DOI: 10.1021/acs.est.5b02749
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Phytotransformation of Benzotriazole Generates Synthetic Tryptophan and Auxin Analogs in Arabidopsis

Abstract: Benzotriazoles (BTs) are xenobiotic contaminants widely distributed in aquatic environments and of emerging concern due to their polarity, recalcitrance, and common use. During some water reclamation activities, such as stormwater bioretention or crop irrigation with recycled water, BTs come in contact with vegetation, presenting a potential exposure route to consumers. We discovered that BT in hydroponic systems was rapidly (approximately 1-log per day) assimilated by Arabidopsis plants and metabolized to nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
170
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(192 citation statements)
references
References 85 publications
16
170
0
Order By: Relevance
“…21 For example, Arabidopsis quickly assimilates and metabolizes benzotriazole and 2-mercaptobenzothiazole in hydroponic media, while carrots and horseradish conjugate the antibacterial agent triclosan. 20, 35, 36, 39 Arabidopsis also takes up and transforms the structurally similar TNT. 9, 22 While the detected phase I and phase II metabolites were not unexpected based on the green liver model and plant metabolism of TNT, the low mass balance of DNAN and phase I metabolites from LC-QQQ analysis indicated that further investigation was required to identify unknown DNAN metabolites.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…21 For example, Arabidopsis quickly assimilates and metabolizes benzotriazole and 2-mercaptobenzothiazole in hydroponic media, while carrots and horseradish conjugate the antibacterial agent triclosan. 20, 35, 36, 39 Arabidopsis also takes up and transforms the structurally similar TNT. 9, 22 While the detected phase I and phase II metabolites were not unexpected based on the green liver model and plant metabolism of TNT, the low mass balance of DNAN and phase I metabolites from LC-QQQ analysis indicated that further investigation was required to identify unknown DNAN metabolites.…”
Section: Resultsmentioning
confidence: 99%
“…20, 43–45 Conjugation proceeds without prior phase I functionalization (e.g., refs 20, 35, 39) or after a phase I reaction. 22 Conjugation with sugars decreases toxicity of the compound and these phase II metabolites are likely intermediates to permanently bound residues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that duckweeds may remove BZT from water (Gatidou et al., ), and other plants are already known to metabolize BZT (e.g., LeFevre et al., , ). We saw stronger decreases in BZT when salt was absent, which could be due to enhanced plant growth and therefore greater biotransformation, or the reverse: greater biotransformation at low salt facilitated enhanced duckweed growth and survival (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…We thus hypothesized (1) that NaCl would magnify negative effects of BZT on duckweeds and microbes. Some microbes and plants cause biotransformation of BZT (Herzog et al, 2013;Kowalska and Felis, 2015;LeFevre et al, 2015), raising the possibility that duckweeds and microbes could potentially be used for bioremediation of this emerging contaminant. Further, microbes can reduce plant salinity stress in several systems (Mayak et al, 2004;Bal et al, 2013;Rho et al, 2018).…”
mentioning
confidence: 99%